ANALYSIS OF FOLKLORE ON ELEMENTARY SCHOOL STUDENTS IN ENVIRONMENTALLY-BASED DISASTER MITIGATION EFFORTS IN THE SOUTHERN COASTAL AREAS OF JAVA ISLAND - Ratnaningsih, Sita; Hady, Yazid; Lesmana, Johan Aristya (UIN Sunan Kalijaga Yogyakarta, 2022)
Folklore as an oral heritage that is entrenched in the community has values that can increase understanding of legends and culture and move people's awareness of the importance of life values. One of them is folklore related to the natural environment. In Indonesia, folklore is not only an oral tradition that is told but also formalized in the education curriculum, especially at the elementary education unit or elementary school level. Folklore that developed in disaster-affected communities was built to provide disaster mitigation education. The purpose of this study was to analyze folklore in elementary school students in an environmentally friendly- based disaster mitigation effort in the Pelabuhanratu Sukabumi area, West Java and Parangtristis Jogjakarta. Using descriptive qualitative methods, this folklore research in elementary schools is discussed using an analysis of disaster mitigation and an environmentally friendly lifestyle. The results showed that folklore contributed to disaster mitigation for elementary school students in Pelabuhanratu Sukabumi and Parangtritis Jogjakarta utilizing several folk stories whose purpose was to build children's understanding and awareness, then for the practical stage it was done through simulation, and for the habituation stage it was done through routines. Values, the values taught are more about protecting the environment to prevent disasters, providing an understanding of the dangers of disasters, and explaining what to do in the event of a disaster.